DESIGNING AN OPTIMAL INVENTORY REPLENISHMENT STRATEGY IN A COMBINED MTS-MTO SUPPLY CHAIN - Kim, Eungap; Min, Daiki (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
We consider a combined MTS-MTO supply chain in which an MTO manufacturer replenishes component inventory from contract suppliers on a MTS basis. Two types of component replenishment strategies are evaluated; multiple suppliers with a fixed order quantity and a single supplier with volume flexibility. For each strategy, we determine an optimal order size, when to place an order for inventory replenishment and an optimal number of suppliers when there are multiple suppliers. This paper formulates the problem as a discrete Markov Decision Process and proposes a solution procedure based on the value iteration algorithm for each strategy. Extensive numerical analysis provides interesting findings. First, the use of an optimal replenishment strategy is dependent not only on the lead-time but also on the traffic intensity and production rate at the MTO manufacturer. Second, the multiple-supplier strategy is likely to outperform the single supplier strategy under heavy traffic intensity, high degree of lead time uncertainty and small size of maximum allowable backorders. Third, the optimal policy for ordering inventory is of the control limit type. Furthermore, the multiple-supplier strategy generally has a lower reorder point than that of the single supplier strategy.